Effect of EFB content on reducibility of low grade iron ore composite at 1000°C - 1200°C - Purwanto, Hadi; Mohd. Salleh, Hamzah; Mohamad, A. S.; Zakiyuddin, A. (Institute of Physics Publishing, 2018)
This paper focus on reduction of low grade iron at high temperature using palm oil empty fruit bunch as a reductant. The samples were crushed and compacted into composite pellet with EFB before drying at 110oC for 24 hours. The reduction test was then conducted by heating the composite pellet in an electric tube furnace. The parameter used was at temperature range 1000oC to 1200oC and under argon gas atmosphere. The efficiency of the empty fruit bunch in the reduction process was investigated based on the extent of reduction of the iron oxide. The results showed that the extent of reduction obtained was 38.97% at 1200oC. This study demostrates that within the temperature range studied, reducibility of low grade iron ore with an empty fruit bunch tends to increase as the temperature increase